The formulation of welfare state: the perspective of Maqāṣid al-Sharī‘ah - Elviandari Elviandari; Farkhani Farkhani; Khudzaifah Dimyati; Absori Absori (IAIN Salatiga, 2018)
This paper examines empirical facts of market failure and government failure toimprove people’s welfare; capitalism and neo-liberalism do not provide a spacefor states to implement policies for social justice. With regard to the failure of thewelfare state to bring the citizen to fair welfare, this paper offers the formulationof a welfare state based on Maqasid Al-Shari‘ah. This study employs Maqasid Al-Shari‘ah developed by Imam Al-Juwaini, Izzu al-Din bin ‘Abd al-Salam, AbuIshaq al-Shatibi and Al-Tahir Ibn ‘Ashur as the methodological framework.It formulates welfare state of maqasid al-shari‘ah, which is built through thefulfillment of the three levels of individual needs (citizens) (al-Daruriyah, alhajiyyah and al-tahsiniyah; primary, secondary and suplementary rights), publicneeds (equal distribution; al-hajah al-‘ammah), protection or assurance (alismah),and law enforcement (al-fitrah (order), equality (al-musawah), freedom(al-hurriyah), magnanimity (al-samhah)). The morality-spirituality-religiosity andtranscendence principles develop the formulation. The maqasid al-shari‘ahshould be the “soul” of every policies and rules or laws. The development ofthe formulation of welfare state based on Maqasid al-Shari‘ah will build Islamicman/religious man (citizen), who is prosperous spiritually and materially.Artikel ini mengkaji kenyataan empiris mengenai kegagalan pasar(market failure) dan kegagalan negara (government failure) dalam meningkatkankesejahteraan rakyat, kapitalisme dan neo-liberalisme tidak memberikantempat bagi negara untuk melakukan kebijakan demi keadilansosial. Berdasarkan kegagalan negara kesejahteraan menghantarkanwarga negara menuju kesejahteraan yang berkeadilan maka tulisan inimenawarkan formulasi negara kesejahteraaan berdasarkan Maqasid al-Shari‘ah. Kajian ini mempergunakan Maqasid al-Shari‘ah sebagai kerangkametodologis yang dikembang oleh Imam Al-Juwaini, Izzu al-Din bin‘Abd al-Salam, Abu Ishaq al-Shatibi dan Al-Tahir Ibn ‘Ashur. Kajian inimemformulasikan negara kesejahteraan berdasarkan maqasid al-shari‘ahyang dibangun melalui pemenuhan kebutuhan individu (warga negara)berdasarkan tingkatannya; al-Daruriyah, al-hajiyyah dan al-tahsiniyah (hakprimer, sekunder dan suplementer), kebutuhan publik, (al-hujah al-‘asmmah) terealisasi pendistribusian yang merata, adanya proteksi atau jaminan(al-ismah) dan tegaknya hukum melalui, al-firah (ketertiban), equality(al-musawah) kesetaraan, freedom (al-huriyah) kebebesan, magnanimity (alsamhah) toleransi. Formulasi tersebut dibangun dengan landasan moral-spritual - religius dan transendental. Menjadikannya “roh” pada setiapkebutuhan dalam membuat kebijakan, peraturan-peraturan atau perundang-undangan. Dengan terwujdnya formulasi negara kesejahteraaanberdasarkan Maqasid al-Shari‘ah akan melahirkan islamic man/manusiareligius/karakter (warga negara) yang beriman atau pribadi yang memilikikarakter, sejahtera secara batin (spritual) dan lahir (material).